Emerging Leaders Video Series - Havens, Jeff (Pearson, 2015)
The fast, fun, and complete video guide to succeeding as a new leader! Description You've identified your company's rising stars ... maybe you're one of them! Either way, you know new leaders are excited at the opportunity to lead#x97;and they wonder just what it'll take to succeed. In Emerging Leaders, Jeff Havens brings together all the knowledge anyone needs to become the kind of leader others want to follow. One of North America's leading presenters on business success, Havens brings fun to the learning process, so his audiences enjoy every minute#x97;and never forget his crucial takeaways. Now, in 20+ minutes of powerfully compelling video, Havens covers everything new leaders need to know up front: how to prepare physically and mentally for a new leadership role ... how to interact more effectively with the people you're leading ... how to develop a vision for your team or organization ... how to strengthen your long-term thinking skills ... how to handle mistakes and failures ... how to motivate people the right way ... how to execute! There's no faster way to supercharge your leadership skills: just watch! About the Instructor A former teacher and stand-up comedian, Jeff Havens has become one of North America's most popular business presenters. His extraordinary ability to deliver high-quality education in an entertaining way has earned him dozens of repeat clients, all of whom appreciate his insistence that education is the only way that we improve at anything, and that we'll all improve better and faster if we enjoy the learning process. By combining traditional presentation content with the entertainment value of a comedy show, Havens has found enthusiastic audiences in government, academia, small businesses, and the Fortune® 50, all while still being one of the youngest members of the professional speaking circuit. A Phi Beta Kappa graduate of Vanderbilt University, he lives in Michigan with his wife, Laura, and their dog, Pancake. He is author of Us vs. Them: Redefining the Multi-Generational Workplace to Inspire Your Employees to Love Your Company, Drive Innovation, and Embrace Change. For more information, visit www.jeffhavens.com . Skill Level Beginner Intermediate What You Will Learn How to prepare both physically and mentally for a new leadership role How to apply successful techniques for interacting effectively with the people you're leading How to bring more vision and deeper long-term thinking to your work as a leader How to overcome the mistakes every ...